Les routes de commercialisation du vin de Narbonnaise : l’apport des épaves profondes au large de la Corse - Franca Cibecchini (Gallia)
Since 2013 Drassm has undertaken the scientific exploration of a series of wrecks located at great depths (300 m/500 m) off the east coast of Corsica. One of these wrecks in particular Macinaggio 1 surveyed in order to be evaluated in 2013, has a homogeneous cargo of Gauloise 4 amphorae associated with a small group of iron bars. This is one of the rare wrecks carrying as main cargo Gauloise 4 amphorae and, as a result, its study, even if partial, allowed a new research approach on the maritime trade of Gallic wine. The expertise of two other wrecks with homogeneous cargoes of amphorae Gauloise 5 in 2015, adds to our knowledge of the trade of Gallic wine by providing new data on these types of amphorae. In fact, the study of these wreck sites, although still preliminary, offers unique information on a trade activity rarely documented by wrecks: the Gallic wine trade between the Flavian period and the time of Trajan.